IMPLEMENTASI PENGGUNAAN APLIKASI WHATSAPP PADA PEMBELAJARAN MEMBACA AL QURAN SISWA KELAS VI DI SDN PLALANGAN 05 KALISAT JEMBER TAHUN 2020/2021: SDN PLALANGAN 05 KALISAT JEMBER - MOKH HAMBALI (Mitra Pendidikan, 2021)
In this pandemic Online learning conducted as an alternative teaching and learning process, Teachers and students cannot meet face to face and it is hoped that learning can still run effectively. There are many problems faced by teachers and students in implementing online or distance learning, including problems of learning motivation costs, networks or services, feedback, lack of experience and so on. Whatsapp media is the most downloaded and used social media in Indonesia by both educators and student s. So Teachers must not explain too much how the using this application. This is reinforced by the results of interviews between teachers and students as reason why they have choosen WhatsApp as a medium for implementing distance learning or PBJJ. Whatsapp media also has many supporting features, including Whatsapp groups, voice notes, sharing photos, video calls (video calls), voice messages, and so on. They can make easier for teachers and students to carry out online learning or PBJJ. And usually the WhatsApp group feature is the teacher's choice to send messages for group members to carry out learning In this research, the researcher used classroom action research by using qualitative approach. This method was chosen because the researcher did not focus on the research results process but prioritized to the conducting research process . Classroom action research can be interpreted as action research in the field of education carried out in the classroom area, From the observations and results of the first cycle of performance, the level of student activity in collecting assignments was 86 percent and the completeness of learning to read the Qur'an only reached 67 percent or below the KKM which was set at 75 percent for Islamic studies. Observations and results of second cyrcle activity students were active levels. 86 percent of students in collecting task and reading Al Quran reached 86 percent or over the KKM which set at 75 percent for Islamic studies. So the research can be summarized that complete.